Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Terhadap Peningkatan Minat Peserta Didik dalam Pembelajaran PAI Kelas XI 2 di SMAN 1 Cluring - Abadi, Ziyan; Kulzum, Putri Maja Mulia; Aldino, Fals (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2023)
This study aims to determine the influence of the Contextual Teaching and Learning (CTL) model on increasing students' interest in learning PAI among grade XI-2 students at SMAN 1 Cluring. This is a quantitative research using a quasi-experimental design with a one-shot case study. The population of this study was all grade XI-2 students at SMAN 1 Cluring, totaling 36 students, and the sample was taken using Simple Random Sampling. A questionnaire was used as an instrument to measure students' learning interest, using Likert scale statements. The results of data analysis can be seen from the percentage of indicators of students' learning interest in PAI, namely: student interaction during learning (73%),student attention to PAI lessons (62%), students' enjoyment of PAI lessons (90%), students' interest in PAI lessons (64%),and students' involvement in learning (61%). This indicates that the CTL learning strategy has an influence on increasing students' interest in learning mathematics. Based on the t-test conducted, it was obtained that -ttable < tcount > + ttable, which is 2.028 < 35 > 2.028, meaning that there is a significant influence of the Contextual Teaching and Learning (CTL) learning strategy on increasing students' interest in learning PAI. From the research findings above, it can be concluded that there is an influence of the Contextual Teaching and Learning (CTL) model on increasing students' interest in learning PAI among grade XI-2 students at SMAN 1 Cluring